Using priming experiments to understand gender attitudes: Lessons from Papua New Guinea and Nepal - Kosec, Katrina; Mo, Cecilia Hyunjung (University of Maryland, 2021)
How do perceptions of relative economic status affect gender attitudes regarding women’s economic participation and decision-making authority in their household and community? Several recent trends highlight the importance of this question. Income inequality within developing countries is on the rise (Ravaillon 2014). Moreover, with the proliferation of social media, permitting quicker comparisons of oneself to others in their network, and increased migration flows, the salience of inequality is simultaneously growing.